PERAN JENIS INDUSTRI SEBAGAI MODERATOR DALAM HUBUNGAN ANTARA UKURAN PERUSAHAAN, LEVERAGE, DAN PENGUNGKAPAN LAPORAN KEBERLANJUTAN: THE ROLE OF INDUSTRY TYPE AS A MODERATOR IN THE RELATIONSHIP BETWEEN FIRM SIZE, LEVERAGE, AND SUSTAINABILITY REPORT DISCLOSURE - Pramudita, Christian Bevan; Ayu, Stephana Dyah (Universitas Riau, 2024)
In line with the PBB policy to establish sustainability as a common international goal, corporate sustainability disclosures are important.This study investigate how company size and leverage can affect the level of corporate disclosure. This study adds industry type as a moderating variable to mitigate research gaps from previous studies. Using 115 companies listed on the IDX, A purposive sampling method was utilized for the sample selection. Data in this study was analyzed using multiple linear regression with SPSS.The results show that the interaction between industry type and company size has a significant effect on the level of disclosure of existing sustainability reports. These results indicate that differences in the type of industry studied will affect the relationship between sustainability report disclosure and its causes. Leverage proved to have a positive influence on disclosure, which means that companies with a larger debt structure disclose more of their sustainability performance. This indicates that sustainability disclosures made by companies are mainly to maintain the company's image so that the company is considered capable of fulfilling its obligations. These results prove that the impression management concept is more appropriate to use to analyze sustainability disclosure in Indonesia